Reduced glutathione and acetylcholinesterase expressions in Perna indica exposed to trivalent arsenic - Rajkumar, J S I (International Journal of Biological Research, 2013)
In the present study Indian brown mussel, Perna indica was exposed to 20, 40, 80, 160 and 320 ppb (µg/l) arsenic concentrations under short-term chronic toxicity bioassay (14 days) for the assessment of reduced glutathione and acetylcholinesterase as potential biochemical biomarkers in arsenic pollution. A higher level of reduced glutathione (GSH) and increased acetylcholinesterase (AchE) activity was expressed when compared to control in 160 and 320 ppb arsenic concentration. The found values were significant at P<0.01. The values of total protein were significantly lower (P<0.05) in all the exposed concentration when compared with control. This study suggests that metabolites and antioxidant enzymes activity was affected by heavy metal exposures and strongly have the potential as indicators of heavy metal contamination and arsenic in specific. Hence, the determination of oxidative stress biomarkers in Perna indica may serve as a convenient approach during pollution biomonitoring programme.